Art Cinema and The Arbor: Tape-recorded Testimony, Film Art and Feminism. Issue 2 (April 2016) - Johnson, Beth
Abstract : In this article I discuss the award-winning work of artist and film-maker Clio Barnard, specifically focusing on her 2010 docu-fiction film The Arbor . Analysing the verbatim techniques so central to the film (techniques that originated in theatre), this article suggests that Barnard's visual arts background inspired and informed her textual mixing of verbatim, lip-sync, re-enactment and digital imaging, the result of which is a radical and feminist art-film. Focusing on the site-specific location of The Arbor as well as the significance of emotional, textual and temporal layering, this article also suggests that while Barnard's work seeks, on the surface, to question the relationship between representation and the real in the genre of documentary, The Arbor also provokes and invites a radical reimagining of the hitherto male-dominated legacy of British art cinema by bringing the voices and visions of women, past and present, into the contemporary frame.